Acute decompensation events differentially impact the risk of nosocomial infections and short-term outcomes in patients with cirrhosis - Xu, Xianbin; Yu, Xia; Gong, Kai; Tu, Huilan; Yao, Junjie; Lan, Yan; Ye, Shaoheng; Weng, Haoda; Shi, Yu; Sheng, Jifang (Frontiers in Medicine, 2022)
Aims: This research aimed to evaluate the influence of acute decompensation (AD) events upon admission on the subsequent risk of nosocomial infections (NIs) and the synergy between AD and the following NIs on the short-term outcome. Methods: A total of 419 hospitalized individuals with cirrhosis and AD participated in the current study. Various AD events at admission and outcomes in patients with or without NIs were compared. The logistic regression and Cox proportional hazards models were designed for NIs development and liver transplant (LT)-free mortality at 28 and 90 days, respectively. Results: During hospitalization, 91 patients developed NIs. Notably, a higher proportion of patients with NIs had jaundice (52.7% vs. 30.5%; p < 0.001) and bacterial infections (37.4% vs. 20.7%; p = 0.001) at admission compared to patients without NIs, while a lower proportion suffered gastrointestinal hemorrhage (16.5% vs. 36.6%; p < 0.001). Multivariate analysis revealed that jaundice was independently linked with the development of NIs (OR, 2.732; 95% CI: 1.104-6.762). The 28-day (16.5% vs. 7.3%; p = 0.008) and 90-day (27.5% vs. 15.9%; p = 0.011) LT-free mortality rates of patients with NIs were significantly higher than those without NIs. According to the Cox proportional hazards model, jaundice remained an independent risk factor for 90-day death (HR, 5.775; 95% CI: 1.217-27.397). The connection between total bilirubin and 90-day mortality was nonlinear, and a 6 mg/mL threshold was proposed. Conclusion: The types of AD events differentially predispose to risk of NIs. Presenting jaundice at admission is independently associated with NIs occurrence and increased 90-day mortality of patients with NIs. Antibiotic prophylaxis may benefit this specific subset of patients.